Developing Instagram Account as Learning Platform of Writing Text Types - Inayatul Ulya (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Developing learning platform of writing was needed in this digital era, it helped students to learn autonomously. This research was aimed to investigate the stages of developing instagram account as learning platform of writing text types and to find out the feasibility of instagram account as learning platform of writing text types. Research and Development (R&D) was implemented in this research. The subject of the research was the second semester students of English Depatment of Pekalongan Universitay. Questionnare was used to get the data and validation of the product. Borg & Gall development model was used in analyzing the data. The result showed the stages of R & D which included some steps, they were research and information collecting of developin instagram account, planning of developing instagram account, develop preliminary of product (instagram account), preliminary filed testing, main product revision, and main field testing. In addition, instagram account was accepted the feasibility validation—it was feasible to be used as learning platform of writing. Moreover, the students were enthusiastic in using instagram as learning platform of writing. They actively involved in joining the discussion in instagram and did writing practices. In conclusion, instagram account was accepted as learning platform of writing text types